Epac1−/− mice have elevated baseline permeability and do not respond to histamine as measured with dynamic contrast‐enhanced magnetic resonance imaging with contrast agents of different molecular weights. (2nd November 2018) - Curry, Fitz‐Roy E.; Taxt, Torfinn; Rygh, Cecilie Brekke; Pavlin, Tina; Bjønrstad, Ronja; Døskeland, Stein Ove; Reed, Rolf K.
Abstract: Aim: Epac1 −/− mice, but not Epac2 −/− mice have elevated baseline permeability to albumin. This study extends the investigations of how Epac‐dependent pathways modulate transvascular exchange in response to the classical inflammatory agent histamine. It also evaluates the limitations of models of blood‐to‐tissue exchange in transgenic mice in DCE‐MRI measurements. Methods: We measured DCE‐MRI signal intensity in masseter muscle of wt and Epac1 −/− mice with established approaches from capillary physiology to determine how changes in blood flow and vascular permeability contribute to overall changes of microvascular flux. We used two tracers, the high molecular weight tracer (Gadomer‐17, MW 17 kDa, apparent MW 30‐35 kDa) is expected to be primarily limited by diffusion and therefore less dependent on changes in blood flow and the low molecular weight tracer (Dotarem (MW 0.56 kDa) whose transvascular exchange is determined by both blood flow and permeability. Paired experiments in each animal combined with analytical methods provided an internally consistent description of microvascular transport. Results: Epac1 −/− mice had elevated baseline permeability relative to wt control mice for Dotarem and Gadomer‐17. In contrast to wt mice, Epac1 −/− mice failed to increase transvascular permeability in response to histamine. Dotarem underestimated blood flow and vascular volume and Gadomer‐17 has limited sensitivity in extravascular accumulation. Conclusion: The study suggests that the normal barrier loosening effect of histamine in venular microvessels do not function when the normal barrier tightening effect of Epac1 is already compromised. The study also demonstrated that the numerical analysis of DCE‐MRI data with tracers of different molecular weight has significant limitations.